2016
DOI: 10.2147/opth.s107594
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-month outcomes in patients with retinal vein occlusion treated with low-frequency intravitreal ranibizumab

Abstract: PurposeThe purpose of this study was to determine the clinical efficacy of low-frequency intravitreal ranibizumab to treat macular edema due to retinal vein occlusion (RVO).Patients and methodsThis was a retrospective examination of cases that received intravitreal ranibizumab for untreated RVO over a period of 12 months. Instead of the conventional three monthly injections, injections were given once during the introductory period. If the recurrence of macular edema was diagnosed during the monthly visit, add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…Another retrospective, observational, multicenter (n = 200) study showed a significant decrease in CMT at 6 months after ranibizumab treatment [37]. Similarly, a significant reduction in CMT was observed in BRVO (n = 21) and CRVO (n = 10) patients after ranibizumab treatment [38]. Overall, the subgroup analysis demonstrates effects of the ranibizumab biosimilar in functional and anatomical visual improvements in BCVA and CMT, and the degree of improvement was similar to that reported in several studies with ranibizumab administration.…”
Section: Discussionmentioning
confidence: 90%
“…Another retrospective, observational, multicenter (n = 200) study showed a significant decrease in CMT at 6 months after ranibizumab treatment [37]. Similarly, a significant reduction in CMT was observed in BRVO (n = 21) and CRVO (n = 10) patients after ranibizumab treatment [38]. Overall, the subgroup analysis demonstrates effects of the ranibizumab biosimilar in functional and anatomical visual improvements in BCVA and CMT, and the degree of improvement was similar to that reported in several studies with ranibizumab administration.…”
Section: Discussionmentioning
confidence: 90%
“…At conclusion of the follow-up period, the 2 groups had similar results in visual outcomes. Skanishi et al evaluated low frequency IVR treatment in ME secondary to RVO, and after a follow-up of 12 months, they reported that patients received mean of 3.4 injections in CRVO group, and 2.1 in BRVO group, which was, again, very low in comparison to multicenter studies (16). Although number of injections was very low, change in VA from baseline to month 6 was reported to be 2.8 lines, and 2.5 lines at month 12 in CRVO group, and 1.8 lines at month 6, and 2.1 lines at month 12 in BRVO group, which were comparable outcomes to aforementioned studies ( Figure 3) (9-13, 16).…”
Section: Discussionmentioning
confidence: 97%
“…Subsequently, various treatment regimens were pursued (9)(10)(11)(12)(13).Loading phase of anti-VEGF drugs has been investigated in some studies, and low-frequency ranibizumab treatment was found to be effective (15). It is worth recalling here that in real-life setting, it is not always possible to conform to strict follow-up and treatment criteria (14)(15)(16)(17)(18)(19)(20). Low visit and injection frequency observed in real life usually leads to decrease in visual and anatomical outcomes in the patients with neovascular age-related macular degeneration (nAMD) or diabetic macular edema (DME) (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations